2022
DOI: 10.4132/jptm.2022.09.29
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive follicular thyroid neoplasm with papillary-like nuclear features: its updated diagnostic criteria, preoperative cytologic diagnoses and impact on the risk of malignancy

Abstract: Due to the extremely indolent behavior, a subset of noninvasive encapsulated follicular variant papillary thyroid carcinomas has been classified as "noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP)" since 2016 and is no longer considered carcinoma. Since the introduction of this new terminology, changes and refinements have been made in diagnostic criteria. Initially, the incidence of NIFTP was estimated substantial. However, the reported incidence of NIFTP varies greatly am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…A recently published epidemiology study using SEER‐22 data, by Chen et al., reported that NIFTP comprised a small fraction of previously diagnosed thyroid cancers, which was significantly less than was anticipated by EPS: 2.2% to 2.6% of thyroid cancers in 2018–2019 vs. 18.6% of PTC estimated by EPS 50 . These data suggest that the impact of NIFTP is not as considerable as initially estimated, and variations in incidence may be a result of variation of cancer rates in different populations, and/or variations in the interpretation of PTC nuclear atypia, which is still subjective despite efforts to objectify it 51 . Therefore, each center should consider basing their clinical decisions on their own data, including incidence of NIFTP in their patient population, and their thresholds for diagnosing PTC 52 …”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…A recently published epidemiology study using SEER‐22 data, by Chen et al., reported that NIFTP comprised a small fraction of previously diagnosed thyroid cancers, which was significantly less than was anticipated by EPS: 2.2% to 2.6% of thyroid cancers in 2018–2019 vs. 18.6% of PTC estimated by EPS 50 . These data suggest that the impact of NIFTP is not as considerable as initially estimated, and variations in incidence may be a result of variation of cancer rates in different populations, and/or variations in the interpretation of PTC nuclear atypia, which is still subjective despite efforts to objectify it 51 . Therefore, each center should consider basing their clinical decisions on their own data, including incidence of NIFTP in their patient population, and their thresholds for diagnosing PTC 52 …”
Section: Discussionmentioning
confidence: 76%
“…50 These data suggest that the impact of NIFTP is not as considerable as initially estimated, and variations in incidence may be a result of variation of cancer rates in different populations, and/or variations in the interpretation of PTC nuclear atypia, which is still subjective despite efforts to objectify it. 51 Therefore, each center should consider basing their clinical decisions on their own data, including incidence of NIFTP in their patient population, and their thresholds for diagnosing PTC. 52…”
Section: Discussionmentioning
confidence: 99%
“…14,20 NIFTP typically shows subtle PTC-like nuclear features which could overlap anywhere on the spectrum of classical PTC and reactive nuclear atypia, though it is generally thought that these tumors need to be managed conservatively with lobectomy instead of total thyroidectomy due to their uncertain malignant potential but likely indolent behavior. 15,19,22,23 While a nuclear scoring scheme could introduce a more structured approach to classification, concerns about intra-and interobserver variability and inconsistent reports remain. 14,24,25 Zajkowska and Strickland addressed the problem with the NIFTP entity.…”
Section: Discussionmentioning
confidence: 99%
“…This uncertainty caused by this wide range and ROM variability demonstrate why molecular techniques are needed to better define the diagnosis and the risks when entities like NIFTP are considered 14,20 . NIFTP typically shows subtle PTC‐like nuclear features which could overlap anywhere on the spectrum of classical PTC and reactive nuclear atypia, though it is generally thought that these tumors need to be managed conservatively with lobectomy instead of total thyroidectomy due to their uncertain malignant potential but likely indolent behavior 15,19,22,23 . While a nuclear scoring scheme could introduce a more structured approach to classification, concerns about intra‐ and inter‐observer variability and inconsistent reports remain 14,24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…The method of estimating the cancer risk, which is based on histologic follow-up, overestimates the ROM, particularly for the categories I–III, where there is selection bias given the relatively small proportion of nodules that undergo excision. Although NIFTP is a surgical disease and cannot be preoperatively diagnosed on CNB or FNA specimens, the morphologic features of NIFTP tend to lead to classification on CNB/FNA as either category III, IV, or V, thereby impacting the resultant ROM calculations [ 13 , 14 , 17 , 18 ]. The ROM for each category is shown when including and excluding NIFTP in malignancy, information that might help guide more conservative clinical management of some nodules.…”
Section: Risk Of Malignancy Of Thyroid Core Needle Biopsy Diagnostic ...mentioning
confidence: 99%